1978
DOI: 10.1073/pnas.75.8.3613
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of ligand-dependent conformational changes in trypsin-solubilized and in membrane particle constrained-acetylcholinesterase.

Abstract: ABSIRACT The effect of a class of ligands on the catalytic activity of acetyicholinesterase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…The acetylthiocholine turnover numbers determined from active site titration with M7C (Rosenberry & Bernhard, 1971) are the same for the phospholipid-associated dimer, the detergent-solubilized dimer (3.0 X 105 min™1, reported herein), and the trypsin-solubilized tetramer reported previously (Pattison & Bernhard, 1978). The specific activity of the purified enzymes is 4000 units/mg for the dimer, 4300 units/mg for the trypsin-solubilized enzyme, and 3400 units/mg for the tailed enzyme.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The acetylthiocholine turnover numbers determined from active site titration with M7C (Rosenberry & Bernhard, 1971) are the same for the phospholipid-associated dimer, the detergent-solubilized dimer (3.0 X 105 min™1, reported herein), and the trypsin-solubilized tetramer reported previously (Pattison & Bernhard, 1978). The specific activity of the purified enzymes is 4000 units/mg for the dimer, 4300 units/mg for the trypsin-solubilized enzyme, and 3400 units/mg for the tailed enzyme.…”
Section: Resultssupporting
confidence: 59%
“…(5) Acetylcholinesterase-enriched suspension ("low-density fraction") was obtained by the following flotation method. Eight milliliters of protein suspension in buffer IV was prepared according to Pattison & Bernhard (1978). The suspension was brought to >40% w/v sucrose by the addition of 80% w/v sucrose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar scenario appears to exist for AChE. Results from several groups indicate that this enzyme is composed of two discrete forms in slow conformational equilibrium and that ligands of the PAS bind only to one form [23,24].…”
mentioning
confidence: 85%
“…A particularly intriguing mode of AchE inhibition was recently uncovered by Pattison & Bernhard (1978), who observed that either rf-tubocurarine in high concentrations or transition metals effect a slow conversion of the enzyme to an inactive state. The use of a fluorescent carbamylating agent enabled these workers to distinguish between inhibition of the initial rate of substrate association and the conversion to nonreactive enzyme.…”
mentioning
confidence: 99%